A test of the trait-interpersonal model of suicide proneness in emerging adults. (November 2016) - Cramer, Robert J.; Moore, Claire E.; Bryson, Claire N.
Abstract: The present study tests the trait-interpersonal model of suicide, an approach integrating both the Five-Factor Model (FFM) of personality and Interpersonal-Psychological Theory of Suicide (IPTS). Survey data in an emerging adult sample ( n = 572) yielded the following prominent predictors of elevated suicide proneness: (1) neuroticism (positively) and openness (positively) predicted suicide proneness (accounting for the IPTS and trait-interpersonal pathways), (2) neuroticism-perceived burdensomeness/thwarted belonging/acquired capability mediation pathways were observed, (3) an extraversion-thwarted belonging pathway emerged, (4) an openness-acquired capability emerged, (5) agreeableness-perceived burdensomeness/thwarted belonging/acquired capability pathways emerged, and (6) conscientiousness-thwarted belonging/perceived burdensomeness pathways were observed. Findings are discussed with regard to trait-interpersonal literature, and public health and clinical suicide prevention strategies. Highlights: Neuroticism-IPTS mediation pathways to suicide were observed. An extraversion-thwarted belonging pathway to suicide emerged. An openness-acquired capability pathway emerged. Agreeableness-IPTS pathways to suicide were observed. Conscientiousness-interpersonal cognition pathways to suicide were observed.